Full-Day School as a Strengthening of Character Education Management for Students - Mauhibur Rokhman; Mochammad Misbakhul Munir (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This article aims to explain the management of character education through the development of full-day school management. This article is a literature review by analyzing the content of relevant books and journals. The results of the discussion of this article are that strengthening management in the implementation of full-day school is able to reduce student delinquency because students are guided and supervised in extracurricular activities or intracurricular activities. Families do not need to worry about the full-day school model because students are under supervision in accordance with the applicable strategic management. Good management can strengthen children's character when supported by exemplary methods. The application of full-day school is an alternative solution for the educational revolution to the problems that occur in the era of globalization. In the process of implementing full-day school, it can also strengthen the management of character education in schools.